Effect of Certification on Adoption and Sustainability of Organic Agricultural Practices - Raphael Mwiti Gikunda; David E. Lawver (Journal of International Agricultural and Extension Education, 2020)
This study highlights the importance of certification on the adoption and sustainability of organic agriculture (OA). The research took place in four counties of Central Kenya; Nyeri, Muranga, Kirinyaga, and Kiambu. Data were gathered from 329 farmers selected through stratified random sampling. A valid and a reliable (sustainability, α = .96; adoption, α = .84)semi-structured questionnaire was used for data collection. MANOVA followed with discriminant analysis was used to establish the differences between certified and non-certified farmers. The adoption levels of pest and disease control, weed, soil, and water management practices were higher among the certified farmers compared to non-certified farmers. Certified farmers also reported higher scores in the three dimensions of sustainability; ecological, social, and economic sustainability. Certification accounted for 15% of the variance in the adoption and sustainability of OA, Ʌ= .85, F(7, 313) = 7.87, p < .05,ηp2=.15. Certification had a large effect on the adoption and sustainability of OA. This can be attributed to need to meet certification and market requirements, better access to extension information, and premium prices attracted by certified produce. Therefore, non-certified farmers should beencouraged to certify their production systems. Increased contacts between farmers and extension agents is also a basic necessity.
Keywords: adoption; certification; organic agriculture; diffusion of innovations; sustainability